Structural analysis of the inhibitory effects of polyphenols, (+)‐hopeaphenol and (−)‐isohopeaphenol, on human SIRT1. (11th December 2018) - Loisruangsin, Arthorn; Hikita, Kiyomi; Seto, Norikazu; Niwa, Masatake; Takaya, Yoshiaki; Kaneda, Norio
Abstract: Human sirtuin 1 (hSIRT1) is a NAD + ‐dependent deacetylase that regulates several cellular processes. Unlike resveratrol, natural polymeric phenolic compounds isolated from Vitaceae are mostly hSIRT1 inhibitors. The resveratrol tetramer, (+)‐hopeaphenol ((+)‐HP), and its geometric isomer, (−)‐isohopeaphenol ((−)‐iHP), were tested for inhibitory effects on purified hSIRT1 using a fluorescent derivative of peptide substrate p53‐AMC ( Fluor de Lys ) and a cofactor NAD + . The Lineweaver–Burk plots indicated that both (+)‐HP and (−)‐iHP were competitive inhibitors against NAD + . Computer‐assisted modeling of the binding of these molecules with hSIRT1 protein provided the most feasible conformation of the enzyme–inhibitor complex. © 2018 BioFactors, 45(2):253–258, 2019